2017
DOI: 10.1007/s00192-017-3475-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prolapse recurrence: systematic review and meta-analysis

Abstract: Levator avulsion, prolapse stage, and family history are significant risk factors for prolapse recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
5
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 48 publications
5
109
5
7
Order By: Relevance
“…Several previous studies have shown an association between avulsions and anterior compartment POP recurrence, even within a relatively short follow‐up time . Not finding such differences in the present study might therefore be surprising.…”
Section: Discussioncontrasting
confidence: 66%
“…Several previous studies have shown an association between avulsions and anterior compartment POP recurrence, even within a relatively short follow‐up time . Not finding such differences in the present study might therefore be surprising.…”
Section: Discussioncontrasting
confidence: 66%
“…distensibility) of the levator ani muscle clearly affects the hiatus causing a change in its dimensions, and hence, it is likely to be one of the etiological factors of POP development. Excessive distensibility of the hiatus, termed ballooning, is associated with occurrence and recurrence of POP.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this review suggest that there is no impact—improvement or deterioration—on PFM function as a result of POP/UI surgery. Given this, and the current lack of evidence to support perioperative PFM training, we may need to be guided by findings from studies that have shown a strong association between poorer preoperative PFM status and poorer postoperative PFM function . Therefore, focusing intervention on women with poor PFM function preoperatively, who are most likely to respond may be the best approach to achieve more effective outcomes from perioperative PFM interventions.…”
Section: Discussionmentioning
confidence: 99%